1995
DOI: 10.1007/bf00192489
|View full text |Cite
|
Sign up to set email alerts
|

Neural pathways involved in mutual interactions between optic lobe circadian pacemakers in the cricket Gryllus bimaculatus

Abstract: The circadian locomotor rhythm of the cricket Gryllus bimaculatus is primarily generated by a pair of optic lobe circadian pacemakers. The two pacemakers mutually interact to keep a stable temporal structure in the locomotor activity. The interaction has two principal effects on the activity rhythm, i.e., phasedependent modulation of the freerunning period and phase-dependent suppression of activity driven by the partner pacemaker. Both effects were mediated by neural pathways, since they were immediately abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In crickets, a circadian clock is located in each optic lobe, and the bilaterally paired clocks mutually interact through a neural pathway (Tomioka et al, 1991;Tomioka, 1993;Yukizane and Tomioka, 1995;Ushirogawa et al, 1997). The clocks control the locomotor activity rhythm to be stably nocturnal, probably by excitatory and inhibitory action to the locomotor center located in the central brain (Tomioka, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In crickets, a circadian clock is located in each optic lobe, and the bilaterally paired clocks mutually interact through a neural pathway (Tomioka et al, 1991;Tomioka, 1993;Yukizane and Tomioka, 1995;Ushirogawa et al, 1997). The clocks control the locomotor activity rhythm to be stably nocturnal, probably by excitatory and inhibitory action to the locomotor center located in the central brain (Tomioka, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…They show circadian rhythms both in spontaneous and light induced responses (Yukizane et al, 2002). Partial destruction of the optic stalk including the MBNs abolishes the circadian locomotor rhythm driven by the optic lobe clock (Yukizane and Tomioka, 1995). Thus the lateral protocerebral areas are the likely output area of the clock signal for driving the locomotor activity.…”
Section: Output Pathway Of the Circadian Clockmentioning
confidence: 99%
“…The circadian clock of this insect is located one in each of the paired optic lobes Chiba, 1984, 1992). The two clocks are mutually coupled to move in synchrony by exchanging coupling signals through a neural pathway Tomioka, 1993;Yukizane and Tomioka, 1995). Immunocytochemistry with anti-Uca -b -PDH antibody revealed that there were widely distributed PDH immunoreactive neurons in the optic lobe.…”
Section: Introductionmentioning
confidence: 99%